Is It Time to Alter the Standard of Care for Iron Deficiency/Iron Deficiency Anemia in Reproductive-Age Women? - Mrutyunjaya B. Bellad; Anmol Patted; Richard J. Derman (Biomedicines, 2024)
Two billion people worldwide suffer from anemia, with reproductive-age women being disproportionately affected. Iron plays a crucial role in cellular function and impacts cognition, physical function, and quality of life. Iron deficiency (ID) and iron deficiency anemia (IDA) are associated with adverse effects on pregnancy and fetal development. Oral iron supplementation has been the standard treatment for decades, often producing sub-optimal outcomes. Many babies are still being born with ID and suffer adverse sequelae due to inadequate iron levels in the mothers. Is it time to consider a broad scale-up of parenteral iron as a new standard of care?